Solid-state gels of poly(p-phenyleneethynylene)s by solvent exchange - Kushida, Soh; Smarsly, Emanuel; Bunz, Uwe H. F. (Macromolecules, 2017)
Solutions of dialkoxy- and dialkyl-poly(p-phenyleneethynylene)s (PPE) form well-defined solid state gels by diffusion of a nonsolvent (SOG), even if the concentration of the PPEs is only 2.5 mg/mL. The residual solvent in the SOG gel does not contain any dissolved PPE according to fluorescence and emissive lifetime measurements. The solvent inside of the gels is confirmed to be more than 90% of the polar solvent, which gives temperature stability to the gel and makes it available for infiltration of analytes, etc. This is in strong contrast to “classic” gels that form by thermal gelation; these still contain dissolved PPE chains. As a result, an ionic-liquid-filled PPE gel could be formed successfully by solvent exchange.
Gesehen am 31.10.2018